(3TQM bGfhf GdJehjd GdYbGQj (B/s - (3WdHI, GfhQs ((3GdGScfOQjI(B: s (3GdecJH GdLGeYj(B, s, 2004)
(3fTGW GdJehjd GdYbGQj , GJaGb GdJehjd , GdVeGf GdYbGQj , Mbhb GdeSJKeQ , Gdhcjd GdYbGQj f GdJfajP Ydi GdYbGQ , GdQbGHI(B.s
Keywords: (3GdJehjds; (3GdYbGQGJs; (3GdYbGQGJ (B- (3bhGfjf h JTQjYGJs